Microbial detection in seroma fluid preceding the diagnosis of breast implant-associated anaplastic large cell lymphoma: a case report and review of the literature. Issue 1 (1st January 2019) - Fricke, A.; Wagner, J. A.; Kricheldorff, J.; Rancsó, C.; Von Fritschen, U.
Abstract: The Breast Implant-Associated Anaplastic Large Cell Lymphoma (BIA-ALCL) represents a topic of great concern. We report the case of a patient with late-onset seroma, who was initially diagnosed with an implant-related infection of the breast due to microbial detection in the seroma fluid, thus delaying the diagnosis of BIA-ALCL.